Ethnographic Insights of Educational Digital Life Behaviours: A Study of Affluent Schools - Ibrahim, Hashim Omar; Al-Hafdi, Fahad Saleem; Alhalafawy , Waleed Salim (Journal of Ecohumanism, 2024)
Recently, many affluent schools have spread, targeting specific classes of learners with the aim of preparing them in qualitative ways that rely primarily on digital educational technologies. The concentrated reliance of this type of schools on digital educational technologies has resulted in the emergence of behaviours prevalent in the educational life of students. Researching and identifying these behaviours in this context related to affluent schools is necessary for working on developing frameworks that enhance understanding of the nature of behaviours associated with digital educational life. Therefore, the current study aimed to conduct qualitative analyses of digital educational life behaviours in affluent schools. The current study is based on the ethnographic approach. Four analytical tools were relied upon, including: daily observations for two full months, analysis of some digital images and video clips that reflect students’ use of digital technologies, semi-structured interviews with teachers, and focus groups with students. The number of teachers was (6) teachers, and the number of students was (6) students. The findings disclosed the presence of (4) behaviours that transform into actual practices through the digital educational life environment in affluent schools, which are: educational ambition, educational satisfaction, independent learning, and affluent learning. It may be important to plan to employ digital technologies to enhance the behaviours and practices of ambition, satisfaction, independent learning, and affluent learning in schools that have intensive technology experiences, whether in affluent schools or regular schools.